Ringing Whooper Swans in Iceland, 1962 - Kinlen, Leo (Wildfowl, 1963)
A party of four spent two weeks in the Arnavatnsheidi (65 55’ N., 20 25’ W), north of Eiriksjkull in western Iceland in August 1962 learning how to catch Whooper Swans for ringing during the period when the adults are flightless due to the moult. Most of the techniques tried failed, owing to the wariness of the swans, their speed in running and their reluctance to leave water in the presence of danger. By chasing or wading into lakes, equipped with swan hooks, we were able to ring and weigh 49 cygnets and 6 adults. Adult weights ranged from 7.4 to 10.3 kg., three breeding birds being heavier and longer-billed than three non-breeders. Cygnet weights ranged from 3.1 to 6.0 kg., average 5.0 kg. The difference in weight between lightest and heaviest members of a brood was greatest in large broods. Brood sizes varied from 1 to 6, averaging 2.8. Two ringed cygnets have so far been recovered: in Co. Down in December 1962 and in Stirling in January 1963. An area of 15 sq miles held at least 40 pairs of Whoopers and 400 non-breeders.